THE PREVAILING FEATURE OF CONSUMER NEEDS IN THE POSTMODERN ERA: CONSUMER NEEDS ANALYSIS IN THE LITHUANIAN MOBILE TELECOMMUNICATIONS SECTOR - Rytel, Tomas (Ekonomika, 2010)
The scientific problem lies in the fact that consumer needs in the postmodern1 era, as a response to the growing significance of the socio-emotional values in contemporary society, are stated rather than examined in a specific industry context to identify the feature of the needs which dominates in consumers within a specific industry. The paper presents an analysis of the motivating consumer needs within the Lithuanian mobile telecommunications sector, enabling identification of the prevailing type of consumers (based on the features of motivation needs), which affects consumer commitment to a specific service provider.This work aims at testing the assumption that the socio-emotional feature dominating in the needs of consumers in the postmodern era is characteristic of the consumer needs in the Lithuanian mobile telecommunications sector. The dominating feature of consumer needs was identified on the basis of the scientific literature examining the concept of postmodern marketing, which reveals the system of needs characteristic of contemporary consumers and its features.The analysis of consumer needs, made in the Lithuanian mobile telecommunications sector, is relevant in that motivating consumer needs are differentiated into the notional types depending on the characteristics of those needs. The practical outcome of the analysis is relevant as it explains the basic causes that determine the consumer commitment and/or buying/consumption decisions.